Організаційно-змістові підходи до підготовки вчителів іноземних мов в університетах США - Леврінц Маріанна; Lőrincz Marianna; Levrints Marianna (Видавництво МДУ, 2020)
Резюме. У статті висвітлюються організаційно-змістові підходи до підготовки вчителів іноземних мов в університетах США, а також особливості укладання змісту освітніх програм. У дослідженні застосовано низку емпіричних методів, а саме тематичний аналіз, контент-аналіз і порівняння. З’ясовано, що зміст іншомовної педагогічної освіти є симбіозом вимог до професійного становлення і розвитку вчителя-філолога, представлених в освітніх стандартах, візуалізації науково-освітньою спільнотою фахових компетентностей, добору репертуару релевантних тематичних курсів та інтересів і потреб студентів і місцевих общин. У статті вперше представлено кількісні характеристики курикулумів програм підготовки вчителів-філологів в американських університетах. Найпопулярнішими дисциплінами є методика викладання ІМ, лінгводидактика, наукове дослідження, оцінювання/моніторинг у навчанні ІМ, застосування інформаційних технологій у навчанні ІМ, планування іншомовного освітнього процесу.

Abstract. The article considers current approaches and practices to the development of curricula of foreign language teacher education programmes in the US universities. The research was conducted with the help of thematic and content analysis which enabled the identification of the distinctive characteristics of curricula of language teacher preparation programmes at the undergraduate and graduate levels. The content of the foreign language teacher education presents itself a symbiosis of requirements towards the preparation and development of prospective teachers as reflected in the relevant standards, mutual visualization of the profession-specific competences, selection of the disciplines needed for the development of respective competences, as well as the students’ and local communities’ needs and interests. The curriculum of language teacher preparation programmes is grouped according to blocks of general, field-oriented and subject-oriented disciplines. The thematic variability of curricula is a key feature of educational programmes. The broadest range of disciplines is represented at the undergraduate level, which becomes more profession focused at the master's level and in certificate programmes. Based on the findings of content analysis, the quantitative characteristics of the curricula of the graduate language teacher education programmes in the US universities were identified. The most popular disciplines are the methods of foreign/second language teaching (100%), second language acquisition (80%), applied linguistics and educational research (77%), assessment and evaluation in the foreign language teaching (67%), the use of information technologies in language teaching and learning (58%), planning of instruction and curriculum design (56%) etc. According to the results of our study, the inherent features of the content of foreign language teacher education are flexibility and adaptability, personalization, differentiation, individualization, interdisciplinary approach, diversity and variability. The aggregated empirical data on quantitative characteristics of teacher education programmes present practical significance for those involved in curriculum design.

Резюме. В статье рассматриваются организационно-содержательные подходы к подготовке учителей иностранных языков в университетах США, а также особенности формирования содержания образовательных программ. Выяснено, что содержание иноязычного педагогического образования является воплощением требований к профессиональному становлению и развитию учителя- филолога, представленных в образовательных стандартах, визуализации научно-образовательным сообществом профессиональных компетенций, отбора репертуара релевантных учебных предметов, интересов и потребностей студентов и местных общин.
Approaches to the development of curricula of foreign language teacher education at the US Universities
Keywords: майбутній учитель; іноземні мови; педагогічна освіта; зміст освіти; навчальний план; університет; США